RESEÑA de : Varios Autores. Lasarte Álvarez (Dir.); Moretón Sanz y López Peláez (Coords.). La protección de las personas mayores. Madrid: Tecnos, 2007 - Donado Vara, Araceli (Revista de Derecho de la UNED (RDUNED), 2008)
-